KESULITAN BELAJAR BAHASA INDONESIA SISWA KELAS V SD NEGERI 13/1 MUARA BULIAN: OBSERVASI DAN WAWANCARA GURU - Marsya; Mutiara Ratu Nirmala; Oliver Chelsea Sitanggang; Khoirunnisa; Silvina Noviyanti (STKIP Subang, 2026)
This study aims to identify and analyze the Indonesian language learning difficulties experienced by fifth-grade students at SD Negeri 13/1 Muara Bulian. A descriptive qualitative approach was employed through classroom observations and in-depth interviews with the class teacher. The findings indicate that students generally demonstrate adequate reading and listening skills, yet face significant challenges in speaking, vocabulary mastery, and identifying the main idea of a paragraph. The dominant contributing factors include regional language interference in daily communication, low motivation for writing tasks, and insufficient variation in instructional strategies. The teacher has employed audiovisual media and repetitive exercises; however, limited media availability remains a barrier. This study recommends the implementation of context-based learning models and sustained literacy reinforcement to address the students' language skill gaps.